2014
DOI: 10.3109/09593985.2013.877112
|View full text |Cite
|
Sign up to set email alerts
|

Weight management including dietary and physical activity advice provided by Australian physiotherapists: a pilot cross-sectional survey

Abstract: Physiotherapists may have an impact on obesity prevention and treatment by providing nutrition and physical activity advice to overweight or obese clients; yet little is known about physiotherapists' beliefs and practices related to client weight management. The aim of this pilot study was to determine the practices, beliefs, attitudes and knowledge of physiotherapists regarding the provision of weight management advice to overweight or obese clients. Physiotherapists (n = 65) working in multiple practice sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…An Australian pilot study showed similar results with 84.6% of physiotherapists saying they provided physical activity advice and 41.5% saying they provided dietary advice (Snodgrass et al, 2014). Physiotherapists in this study also reported using observation (60.0%) or BMI (47.7%) to determine whether patients were overweight; however, they tended to use weight in kilograms as a monitoring outcome measure.…”
Section: Intensified Focus On Weight Managementsupporting
confidence: 63%
See 3 more Smart Citations
“…An Australian pilot study showed similar results with 84.6% of physiotherapists saying they provided physical activity advice and 41.5% saying they provided dietary advice (Snodgrass et al, 2014). Physiotherapists in this study also reported using observation (60.0%) or BMI (47.7%) to determine whether patients were overweight; however, they tended to use weight in kilograms as a monitoring outcome measure.…”
Section: Intensified Focus On Weight Managementsupporting
confidence: 63%
“…Similarly, in a survey of Australian physiotherapists, Snodgrass et al (2014) found that over 80% of participants considered weight management to be part of their scope of practice. Interestingly, in the same study, under 20% of the participants reported receiving any formal training in weight management.…”
Section: Intensified Focus On Weight Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, there is a need for more focused research in the area, which can inform the creation of healthcare practices that better support individuals in achieving health and wellness (independent of body weight). This is of particular relevance for physiotherapists who are frequently involved in such anti-obesity programs (Snodgrass, Carter, Guest, Collins, James et al, 2014). With this goal in mind, we used a critical-embodiment lens to examine experiences of a lifestyle intervention for teens.…”
Section: Introductionmentioning
confidence: 99%